PENGEMBANGAN TES MODEL TIMSS UNTUK MENGUKUR KEMAMPUAN NUMBER SENSE SISWA SEKOLAH MENENGAH PERTAMA - Nurdiana, Riyanti; Hartoyo, Agung; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTIMSS results in the number content and number sense ability of students in Indonesia are still low. This research aims to train and familiarize students of the junior high school to work on problems in TIMSS using numbers sense abilities. The process of developing test instruments in this research through the stages of the Plomp development model are (1)preliminary investigation phase; (2) design phase; (3) realization phase; (4) test phase, evaluation and revision, and (5) implementation phase. This research produces good quality test. The test instrument has met the criteria for valid, reliable, objective and practical included 4 item with high validity categories and 14 items of medium validity categories; the level of reliability is very high with r11 = 0.884, objective from the results of reliability and practical from the student response questionnaire analysis with the average student giving a positive response of 72.1%. The results of the research reveal the test instruments that can measure the number sense ability is in the low category with an average percentage in the overall number sense indicator of 44.26% and from the interview results students have not used all the indicators of the number sensing ability well. Keywords: Development of Plomp, TIMSS Test, The Ability of The Number Sense